Arguing The Just War in Islam. By John Kelsay. Harvard University Press2007. Pp.263. $24.95. ISBN: 0-674-0263 9-X. - Carnahan, Kevin (Journal of law and religion, 2008)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS074808140000206X/resource/name/firstPage-S074808140000206Xa.jpg